Order your happiness now! - Fan, Shu Fen (2008)
The project is about a 20 minute short movie on a fictitious sexual enhancement product for women - the Aonder Pill. the video chronicles the life of Wonder Pill, from its conception to its sudden demise as well as the effects that it had on Singaporeans.